(untitled) (Annals of Medical Research, 2023)
Aim: In this study conducted in a single tertiary care center, it was aimed to examine the sociodemographic, clinical, biochemical, microbiological and follow-up results of cellulitis patients. Materials and Methods: Demographic characteristics, presence of predisposing factors, cellulitis involvement area, attack characteristics, hospitalization status/duration, agents used in treatment and their durations, tissue/wound/blood culture, biochemistry and ultrasonography characteristics of the patients were examined and the results were compared by grouping the patients according to first attack/recurrent attack, inpatient/outpatient treatment, presence of concomitant diabetes and obesity. Results: In the recurrent attack group, the frequency of diabetes, obesity, venous insufficiency, lymphedema and onychomycosis were significantly higher than in the initial attack group (p values; <0.001, <0.001, 0.025, <0.001, 0.002, respectively). The prevalence of obesity, diabetes mellitus and changing the initial antibiotic was significantly higher in the inpatient group compared to the outpatient group (p values; <0.001, 0.004, <0.001, respectively). Conclusion: Diabetes, obesity, venous insufficiency, lymphedema, and conditions that impair skin integrity are important predisposing factors for both the development and recurrence of cellulitis.